2011
DOI: 10.1001/archsurg.2011.233
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Palliation in Patients With Incurable Malignant Colorectal Obstruction by Means of Self-expanding Metal Stent

Abstract: To evaluate the short-and long-term efficacy of self-expanding metal stents (SEMSs) in patients with colorectal obstruction and incurable cancer and the related factors that affect outcomes. Design: Retrospective analysis of SEMS placement for incurable colorectal obstruction in a 3-year period. Setting: Five tertiary care endoscopic centers. Patients and Intervention: Consecutive patients (N=201) undergoing stenting for incurable malignant obstruction. Main Outcome Measurements: Clinical and technical success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 24 publications
10
82
0
7
Order By: Relevance
“…In contrast, one study conducted in the same year as the previously cited randomised trial and using the WallFlex stent was associated with a perforation rate below 5% (19), which is in line with previous studies using other stents (11,14,20). The results of prospective trials and of recent retrospective studies further demonstrated the effectiveness of SEMS in the palliative management of malignant colorectal obstruction (6,7,(12)(13)(14)21). In this study, sustained relief of obstructive symptoms without reintervention was the primary outcome.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, one study conducted in the same year as the previously cited randomised trial and using the WallFlex stent was associated with a perforation rate below 5% (19), which is in line with previous studies using other stents (11,14,20). The results of prospective trials and of recent retrospective studies further demonstrated the effectiveness of SEMS in the palliative management of malignant colorectal obstruction (6,7,(12)(13)(14)21). In this study, sustained relief of obstructive symptoms without reintervention was the primary outcome.…”
Section: Discussionsupporting
confidence: 88%
“…These results, however, conflict with other studies reporting short-and longterm clinical failure in more than 50% of patients, along with a high number of severe complications (4,5). Furthermore, several risk factors have been associated with stent patency, complications and clinical outcomes, as well as with conflicting results (1,6,(12)(13)(14). The question remains: are SEMS used for definitive palliation of malignant colorectal obstruction as successful as those used as a bridge to surgery?…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…15,55 Early perforation necessitates emergency surgery and may be associated with high mortality (reported as 50% in prospective and retrospective studies. 56,57 Stent migration and re-obstruction (caused by either tumour in-growth or inadequate stent expansion) can usually be managed endoscopically. Stentin-stent placement has reported success rates of 75% to 86% but there is a lack of data on long-term outcomes.…”
Section: Palliative Semsmentioning
confidence: 99%
“…Retrospective series suggested an increased perforation rate in those treated with bevacizumab (an angiogenesis inhibitor) (17%-50%). 22,57,59 A recent meta-analysis investigated risk factors for increased perforation rate. 25 Chemotherapy without bevacizumab was not associated with a significantly increased risk (7.0%), but use of bevacizumanb was (12.5%).…”
Section: Palliative Semsmentioning
confidence: 99%